ALAT MONITORING SUHU DAN KELEMBABAN UNTUK RUANGAN CT SCAN DI INSTALASI RADIOLOGI BERBASIS IOT DENGAN FITUR ALARM: IoT Based Temperature and Humidity Monitoring System with Alarm for CT Scan Rooms in Radiology Installations - Reni Septriani; Danang Widyawarman (Politeknik Unggulan Kalimantan, 2026)
Radiology services in hospitals are an integral part of the healthcare system, with CT-Scan being one of the primary modalities. The CT-Scan room requires a highly controlled environment, specifically a temperature range of 20–24°C and humidity level between 40–60%, to ensure optimal equipment performance and image quality. Excessive humidity can lead to condensation, which risks damaging expensive electronic and optical components and may compromise imaging results. Therefore, an Internet of Things (IoT)-based temperature and humidity monitoring system with real-time alarm features has been developed for the CT-Scan room at the Radiology Installation of Sultan Suriansyah Regional Public Hospital. This device is designed to issue alerts when humidity reaches or exceeds 60%, and enables remote, real-time monitoring through a web-based interface. Test results indicate that the system operates stably and accurately, transmitting online data with less than ±5% deviation compared to a reference device (thermophygrometer). The system has proven effective in maintaining the environmental conditions of the CT-Scan room, improving operational efficiency, and supporting the reliability of medical equipment. With IoT integration, monitoring can be conducted anytime and anywhere, strengthening preventive maintenance and enhancing the quality of radiology services.